Strategi promosi perpustakaan desa dalam merawat eksistensi di masa kini - Sawiti, Ahmad; Fathullah, Amal (Pustaka Karya : Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
This research aims to uncover the promotional strategies used by the Berkat Ilmu Village Library in Tambak Sirang Laut Village, Banjar Regency, South Kalimantan Province, to remain relevant in the era of digitization. This study is a qualitative field research with the object of research being the promotional strategies of the Berkat Ilmu Village Library in Tambak Sirang Laut Village. The subjects of the study are the Head of the Berkat Ilmu Village Library and two library staff members. Data collection techniques include interviews, observations, and documentation. Data analysis involves three stages: data reduction, data presentation, and drawing conclusions. The research findings reveal that the promotion of the Berkat Ilmu Village Library in Tambak Sirang Laut Village includes creating the name "Berkat Ilmu" for the village library, establishing collaborations with various stakeholders, active presence on social media, organizing competitions at the library on important days, and providing mobile library services. The hindering factors for the promotional strategies of the Berkat Ilmu Village Library in Tambak Sirang Laut Village include two aspects: lack of funding and a shortage of human resources in terms of quality.